miyoko23q3

2021-11-17

Solve Equation with Fraction or Decimal Coefficients. In the following exercises, solve each equation by clearing the fractions.

$\frac{3}{4}a-\frac{1}{3}=\frac{1}{2}a+\frac{5}{6}$

Ryan Willis

Beginner2021-11-18Added 15 answers

Consider the equation,

$\frac{3}{4}a-\frac{1}{3}=\frac{1}{2}a+\frac{5}{6}$

In order to find the solution follow the steps given below:

First find the least common denominator of all the fractions.

Then, multiply both sides of the equation by the least common denominator.

Then, use Distributive Property which states that for any real numbers a, b and c,$a(b+c)=ab+ac$ .

Then simplify.

The least common denominator is 12.

So,$12(\frac{3}{4}a-\frac{1}{3})=12(\frac{1}{2}a+\frac{5}{6})$

$12\left(\frac{3}{4}a\right)-12\left(\frac{1}{3}\right)=12\left(\frac{1}{2}a\right)+12\left(\frac{5}{6}\right)$

$9a-4=6a+10$

$9a-4-6a+4=6a+10-6a+4$

Solve further to get,

$3a=14$

$\frac{3a}{3}=\frac{14}{3}$

$a=\frac{14}{3}$

Hence,$a=\frac{14}{3}$ is the solution of $\frac{3}{4}a-\frac{1}{3}=\frac{1}{2}a+\frac{5}{6}$ .

In order to find the solution follow the steps given below:

First find the least common denominator of all the fractions.

Then, multiply both sides of the equation by the least common denominator.

Then, use Distributive Property which states that for any real numbers a, b and c,

Then simplify.

The least common denominator is 12.

So,

Solve further to get,

Hence,